Multi-pole modeling and simulation of an electro-hydraulic servo-system in an intelligent programming environment - Grossschmidt, Gunnar; Harf, Mait (International Journal of Fluid Power, 2016)
The paper presents composing of models and simulation of an electro-hydraulic servosystem, including hydraulic servo-drive with feedback regulator, electro-hydraulic servo-valve and constant pressure feeding system with variable displacement pump. For composing mathematical models of the fluid power system multi-pole models with different oriented causalities are used. Using multi-pole models allows describe models of required complexity for each component. Using a Java based intelligent programming environment CoCoViLa as a tool, enables one graphically describe multi-pole models of the system and perform imulations in a user-friendly manner. Solving large equation systems during simulations can be avoided. Models of four-way sliding spool throttling slot pairs describe open slot and overlapped slot characteristics of various causalities. For correcting the control signal to the electro-hydraulic servo-valve a non-linear differential regulator is used. An intelligent simulation environment CoCoViLa supporting declarative programming in a high-level language and automatic program synthesis is shortly described. It is convenient to describe simulation tasks visually using visual images of multi-pole models. The designer does not need to focus on programming, but instead can use the models with the generated code. Simulations of subsystems of electro-hydraulic servo-system and the entire system are considered and simulation results are presented and discussed.